Failure behavior around a circular opening in a rock mass with non-persistent joints: A parallel-bond stress corrosion approach - Yang, Xu-xu; Jing, Hong-wen; Chen, Kun-fu; Yang, Sheng-qi (Journal of Central South University, 2017)
The stability of underground excavations is influenced by discontinuities interspaced in surrounding rock masses as well as the stress condition. In this work, a numerical study was undertaken on the failure behavior around a circular opening in a rock mass having non-persistent open joints using PFC software package. A parallel-bond stress corrosion (PSC) approach was incorporated to drive the failure of rock mass around the circular opening, such that the whole progressive failure process after excavation was reproduced. Based on the determined micro parameters for intact material and joint segments, the failure process around the circular opening agrees very well with that obtained through laboratory experiment. A subsequent parametric study was then carried out to look into the influence of lateral pressure coefficient, joint dip angle and joint persistency on the failure pattern and crack evolution of the rock mass around the circular opening. Three failure patterns identified are step path failure, planar failure and rotation failure depending on the lateral pressure coefficient. Moreover, the increment of joint dip angle and joint persistency aggravates the rock mass failure around the opening. This study offers guideline on stability estimation of underground excavations.